2018
DOI: 10.1039/c8ra01027g
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine-coated graphene nanosheets as efficient electrocatalysts for oxygen reduction reaction

Abstract: Polydopamine-coated graphene nanosheets show excellent electrocatalytic activity towards oxygen reduction reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Thus, they used GO@PDA as an electrocatalyst for oxygen reduction. Compared with Pt-based catalysts, the GO@PDA exhibited better stability and methanol resistance . In another study by Zhang et al , GO@PDA was utilized as a separation membrane .…”
Section: Surface Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, they used GO@PDA as an electrocatalyst for oxygen reduction. Compared with Pt-based catalysts, the GO@PDA exhibited better stability and methanol resistance . In another study by Zhang et al , GO@PDA was utilized as a separation membrane .…”
Section: Surface Modificationmentioning
confidence: 99%
“…Compared with Pt-based catalysts, the GO@PDA exhibited better stability and methanol resistance. 106 In another study by Zhang et al, GO@PDA was utilized as a separation membrane. 107 They reported that the PDA coating could modulate the microstructure of GO and the size of membrane nanochannels.…”
Section: Surface Modificationmentioning
confidence: 99%
“…As shown in Figure 1 c, a sharp diffraction peak (2θ = 11.7°) was assigned to the 002 plane of GO with d-spacing of 0.95 nm. After adding PDA, the peak shifts to smaller angle (2θ = 10.8°), indicating the decrease of d-spacing [ 42 ]. As for HNTs, by the addition of PDA, no chemical reaction occurs between the nanotubes and PDA.…”
Section: Resultsmentioning
confidence: 99%
“…Considering other catalysts, PDA/rGO showed an excellent durability in 70 000 cycles in the oxygen reduction reaction with remaining current densities of 83 % . A Ag 0 ‐PDA/Fe 3 O 4 preparation gave an average yield of 98 % in 27 repeated uses in the decomposition of methylene blue .…”
Section: Discussionmentioning
confidence: 99%
“…The final example is about the fabrication of PDA/reduced graphene oxide (rGO) composites by reacting GO nanosheets and dopamine/Tris (85 °C, 75 h) . GO is usually prepared by the Hummers method (oxidizing graphite powder with KMnO 4 in a solution of conc.…”
Section: Utilization Of Pda As Organocatalystmentioning
confidence: 99%